Why is There Low Morbidity and Mortality of COVID-19 in Africa? - Njenga, M Kariuki; Dawa, Jeanette; Nanyingi, Mark; Gachohi, John; Ngere, Isaac; Letko, Michael; Otieno, C F; Gunn, Bronwyn M; Osoro, Eric (The American journal of tropical medicine and hygiene, 2020)
Three months since the detection of the first COVID-19 case in Africa, almost all countries of the continent continued to report lower morbidity and mortality than the global trend, including Europe and North America. We reviewed the merits of various hypotheses advanced to explain this phenomenon, including low seeding rate, effective mitigation measures, population that is more youthful, favorable weather, and possible prior exposure to a cross-reactive virus. Having a youthful population and favorable weather appears compelling, particularly their combined effect; however, progression of the pandemic in the region and globally may dispel these in the coming months.